A Cross Sectional Study of Behavioral Risk Factors of Coronary Heart Disease among the Rural Population of Karnataka, South India - Mendagudli, Roopa R; Akka, Kirankumar D; Dorle, Ashok S; Nigudgi, Shantkumar R (National Journal of Community Medicine, 2017)
Background and Objectives: Lifestyles of populations across the world have changed dramatically in the 20th century. This epidemiologic transition has led to the rapid rise in the burden of cardio vascular diseases in developing countries. The present study was undertaken to find out the behavioral risk factors of Coronary Heart Disease (CHD) in the rural South Indian population of Bagalkot, Karnataka. Methods: A cross sectional study was conducted in Shirur, the rural field practice area of S. Nijalingappa Medical College, Bagalkot from 1st January 2011 through 31st October 2012. The data was collected by house to house survey using a pre-designed, semi structured proforma. The study for prevalence of the behavioral risk factors of CHD was conducted among a sample of 1226 respondents aged 20 years and above selected by systematic random sampling method. Results: The prevalence of CHD was found to be 7.58% which was significantly associated with nature of work, mixed diet consumption, smoking, central obesity and history of hypertension. Conclusion: The higher prevalence of CHD in Shirur, a rural area of North Karnataka is a matter of concern and CHD was found significantly associated among hypertensive, those with positive family history of hypertension, among those consuming mixed diet, smokers, sedentary physical activity.